2000
DOI: 10.1086/317614
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Echinocandin Analogue Caspofungin on Cell Wall Glucan Synthesis byCryptococcus neoformans

Abstract: The echinocandin derivative caspofungin (MK-0991, L-743,872) inhibits 1,3-beta-d-glucan synthesis and is active against several medically important fungi but is relatively ineffective against Cryptococcus neoformans. To investigate the mechanism of C. neoformans resistance, the prevalence of 1,3- and 1,6-beta-d-glucan linkages was determined in cells grown with and without caspofungin, using affinity-purified antisera and gold particle immunoelectron microscopy. Cryptococcal strains ATCC 24067 (serotype D) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 15 publications
3
84
0
2
Order By: Relevance
“…Using an in vitro (1,3)-␤-glucan synthase activity assay, this possibility was ruled out: C. neoformans (1,3)-␤-glucan synthase activity was determined to be very sensitive to the echinocandins, with an apparent caspofungin K i of 0.17 Ϯ 0.02 (mean Ϯ standard deviation) M and cilofungin K i of 22 Ϯ 5.7 M (114). Consistent with these results, caspofungin has been shown to reduce both ␤-(1,3) and ␤-(1,6) glucan linkages in the C. neoformans cell wall (65). Other possible explanations for the resistance to echinocandins include rapid efflux from the cell, for example, by multidrug transporters, or the echinocandins could be degraded, either extracellularly or intracellularly.…”
Section: Resistance To Drugs Exerting Cell Wall Stressmentioning
confidence: 53%
“…Using an in vitro (1,3)-␤-glucan synthase activity assay, this possibility was ruled out: C. neoformans (1,3)-␤-glucan synthase activity was determined to be very sensitive to the echinocandins, with an apparent caspofungin K i of 0.17 Ϯ 0.02 (mean Ϯ standard deviation) M and cilofungin K i of 22 Ϯ 5.7 M (114). Consistent with these results, caspofungin has been shown to reduce both ␤-(1,3) and ␤-(1,6) glucan linkages in the C. neoformans cell wall (65). Other possible explanations for the resistance to echinocandins include rapid efflux from the cell, for example, by multidrug transporters, or the echinocandins could be degraded, either extracellularly or intracellularly.…”
Section: Resistance To Drugs Exerting Cell Wall Stressmentioning
confidence: 53%
“…Although the biosynthetic pathways of both ␤-(1,3)-and ␤-(1,6)-glucans are differently regulated, data presented here and in other studies show that the synthesis of these two glucan polymers seem coordinated. Reduction of ␤-(1,3)-glucan either seen in different mutants or consecutively to the addition of ␤-(1,3)-glucan synthase inhibitors is associated to a diminishment of the ␤-(1,6)-glucan content of the cell wall (54,56,57). These results suggested that ␤-(1,6)-glucan synthesis anchored neosynthesized ␤-(1,6)-glucan to ␤-(1,3)-glucan.…”
Section: Discussionmentioning
confidence: 99%
“…The cell integrity-defective ccr4⌬ mutant was found to be sensitive to caspofungin, an echinocandin antifungal to which C. neoformans exhibits intrinsic resistance (12). Cell integrity is currently the target of the majority of antifungal agents in use.…”
Section: Discussionmentioning
confidence: 99%
“…C. neoformans, however, exhibits a high level of intrinsic resistance to this class of drug (12). The cell integrity defects of the ccr4⌬ mutant led us to hypothesize that loss of CCR4 sensitized C. neoformans to the antifungal echinocandin caspofungin.…”
Section: Fig 2 (A)mentioning
confidence: 99%